JARINGAN KAWIN LARI DI KOTA PADANG; Aktor, Pola Kerja, dan Respon Pemerintah - Amri, Mufti Ulil (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This article describes about the network of “eloping” located in Padang. Eloping is often be an alternativefor some married couples who obstructed due to various factors, such as parent’s disagree, polygamy withoutpermission, or the difficulty of the affairs of marriage because of custom. Padang is a place for some coupleselope. Initial search showed that there are at least two areas that are often targeted, namely Lubuk Buaya andBungus Teluk Kabung. The marriage certificate obtained from this process is the original marriage certificateissued by the Ministry of Religious Affairs. However, KUA address listed in most cases are not in Padang, butin districts located in Kerinci, Jambi. This fact indicates that the network actors are quite strong in Padang.Based on that need to be asked: what kind of elopement network that built up in Padang? Who are the actors?How does it work patterns? And how the government's response to this issue? To answer this question, the datawere collected through interviews, observation and document study. As an initial step, this article presents thedescriptive data and qualitative analysis.